PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN: EFEK MEDIASI BURNOUT (Studi Pada Karyawan PT. SAPTA Sari Tama Cabang Banjarmasin) - Yohan Indrawan; Meiske Claudia; Ahmad Rifani (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
This study aims to determine the relationship between workload (X1) and work stress (X2) on employee performance (Y) with the effect of mediation burnout (Z) on the employees of PT. Sapta Sari Tama Banjarmasin Branch. This research method uses a sampling technique which is a sampling technique where all members of the population are used as samples with 33 employees of PT Sapta Sari Tama Banjarmasin branch obtained by survey method by giving questionnaires to respondents. Measurement of variables is measured using scale Likert with a weighting scale from 1 to 5. The method of analysis in this study using Partial Least Square is considered fitting with this study which only has 33 respondents. Based on research data it can be concluded that workload has no effect on burnout employee, but workload has an effect on employee performance. Work stress affects burnout employee, but work stress does not affect employee performance. While burnout has no effect on employee performance and employee performance is not affected by work stress or burnout employee, because employees are aware that the company will provide compensation in accordance with the work they do. The results of the study found that there is an influence of work stress on burnout employee with support between employees and superiors can be a motivation so that employees can contribute better. Future studies, should be added to some variables such as compensation and motivation which influence on employee performance.